PENGGUNAAN CITRA LANDSAT 8 UNTUK PEMETAAN PERSEBARAN LAMUN DI PESISIR PULAU BATAM - Lubis, Muhammad Zainuddin; Sari, Dewi Puspa; Aprilliyanti, Titi; Daulay, Ari Kurniawan; Hanafi, Aditya; Ananda, Fitriya; Saputri, Dhea Ayu; Aminah, Siti; Zabid, Muhammad Anand Pratama; Ibrahim, Muhammad Ma'ruf (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2017)
Landsat 8 satellite provides information (image / picture / photo map) operating free which can be downloaded from the official website. Lyzenga analysis is used to correction of water column so that the appearance of the object in satellite sensors for the better. The study was conducted during the month of August 2016 using the method with Lyzenga, proofreading imagery, as well as classification. The purpose of this research is to know the distribution of sea grass in coastal areas of the island of Batam using Landsat 8, by looking at the physical parameters of the ocean in-situ temperature and dissolved oxygen (DO). These results indicate the relationship of the distribution of each station has the lowest value that is at Piayu sea, and the highest brightness values are in the area of Nongsa sea, dissolved oxygen (DO) is highest in the area Piayu sea and the highest temperature in the area Sekupang sea with a value of 80 mg/l and 36.50 C. His cause is not found in mono-specific sea grass life and the area, and there are no real ecological disturbances, such as the characteristics of the habitat, community structure, and the threat of sea grass distribution plan participate discussed.